MicroRNAs in the etiology of colorectal cancer: pathways and clinical implications - Ashlee M. Strubberg; Blair B. Madison (The Company of Biologists, 2017)
MicroRNAs (miRNAs) are small single-stranded RNAs that repress mRNA translation and trigger mRNA degradation. Of the ∼1900 miRNA-encoding genes present in the human genome, ∼250 miRNAs are reported to have changes in abundance or altered functions in colorectal cancer. Thousands of studies have documented aberrant miRNA levels in colorectal cancer, with some miRNAs reported to actively regulate tumorigenesis. A recurrent phenomenon with miRNAs is their frequent participation in feedback loops, which probably serve to reinforce or magnify biological outcomes to manifest a particular cellular phenotype. Here, we review the roles of oncogenic miRNAs (oncomiRs), tumor suppressive miRNAs (anti-oncomiRs) and miRNA regulators in colorectal cancer. Given their stability in patient-derived samples and ease of detection with standard and novel techniques, we also discuss the potential use of miRNAs as biomarkers in the diagnosis of colorectal cancer and as prognostic indicators of this disease. MiRNAs also represent attractive candidates for targeted therapies because their function can be manipulated through the use of synthetic antagonists and miRNA mimics.